O Rio que mora no mar: a Bossa-Nova na construção da marca turística do Rio de Janeiro . - Bückmann, Ingrid (2022)
This research studies constructive elements of the brand of Rio de Janeiro - its plurality, attributes, and universe of images - specifically from the lyrics of Bossa-Nova songs, and speculates if this movement has influenced the attributes that consolidated Rio de Janeiro as a brand and as a touristic destination. Concepts of branding and its applications for places and cities were considered, relating them with emblematic data from the history of tourism in Rio de Janeiro and issues associated with creative tourism in contemporary times. Furthermore, the research focuses on the Bossa Nova movement and its relationship with the city. Thus, a content analysis of 312 song lyrics was carried out based on Laurence Bardin's methodology, two semi-structured interviews with Roberto Menescal and Ricardo Cravo Albin, and a survey that sought to assess the knowledge of today's young people about Bossa Nova. The investigation concludes that Rio de Janeiro did not know how to take advantage of the potential of this musical style as other cities were able to do with their peculiar rhythms. Therefore, and considering the characteristics of the professional master's modality, the research finally proposes an application that helps promote Rio de Janeiro as a tourist destination through its association with Bossa Nova